Understanding landscape dynamics using spatial metrics: A case of Maseru City Council (MCC), Lesotho - Ramotubei, Pheello (School of Architecture, Planning and Geomatics, 2019)
Remote sensing provides accurate and timely data for earth’s change detections for better decision making. Both land use and land covers (LULC) are important dynamics in understanding the dynamics interaction between human activities and the environment and the changes within the environment due to these interactions. Rapid population growth together with an irreversible process of urbanisation results in productive agricultural land which serves as the main source of livelihood under pressure for residential purposes. The reason being rapid urbanisation led to rapid increase of informal settlement in the developing countries and hence information about location and the extent of these informal settlements is needed to guide resources allocation distribution for upgrading and decision making processes. Thus a quantitative measure like the spatial metrics is used in this research to provide information on the rate and pattern of urban expansion for urban planners to device a mechanism for proper spatial planning and provide a management policy direction for solving complex problem of population growth and the encroachment of the informal settlements into fertile agricultural land along the urban peripheries emanating from internal and international migrations. The study indicates that there has been an increase of 928 Ha in the built up land between 2005 and 2016, while at the same time the agricultural has decreased by 820 Ha at the expense of the built up land. This indicates that in 11 years, percentage decrease of 0.35% in agricultural land is lost for built up land annually. In the similar manner, around the urban peripheries there is a loss of 3.4% of agricultural land (60.36 Ha) annually for informal settlement between 2005 and 2016 The spatial metrics which provide the quantitative description of composition and configuration of landscape shows that the urban peripheries are gradually being transformed from being simple compact to being more fragmented and complex as indicated by Area Weighted Mean Patch Fractal Dimension (AWMPFD) greater than one. This study indicates a need for immediate intervention through planned settlement to cater for an ever increasing population growth from natural birth and different types of migrations.